AN INVESTIGATION OF EFFECTIVENESS OF SIMULATION IN DEVELOPING ORAL SKILLS: A CASE STUDY - Javid, Choudhary Zahid (European Scientific Journal, ESJ, 2013)
One of the foremost challenges that confront English language teachers is the use of innovative and practical teaching techniques to make their students learn effectively and efficiently. Much research has offered deep insights into the fact that the power of simulation can transpose the normal classroom into an authentic setting where language skills can be taught under more realistic conditions. The rationale and purpose behind this research study was to implement this modern technique of simulation in English language teaching to freshman students of pharmacy. The sample of this study comprised of the whole population of freshman pharmacy students at Taif University. The experimental group was taught by using integrated simulation activities in their English language classes. The control group was taught without this innovation. The pre-intervention and post-intervention scores have been analyzed that have clearly reported that the experimental group out-performed the control group in their oral communication. But the results of both the groups in their listening skills quizzes have not showed significant differences. The research suggests that ELT faculty members should use this innovative teaching technique especially in their oral communication classes.